2018
DOI: 10.1021/acscentsci.8b00706
|View full text |Cite
|
Sign up to set email alerts
|

Acid Trip: Zika Virus Goes Off-Pathway during pH-Triggered Membrane Fusion

Abstract: Single-virus measurements reveal unusual details of Zika and liposome fusion, suggesting an off-pathway mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Despite intensive global efforts, no specific treatment for ZIKV-associated diseases is currently available, which partially may be attributed to an incomplete understanding of the infection process. , Curcumin, a natural compound with pleiotropic activity, has demonstrated broad-spectrum antiviral properties. Experimental data have confirmed that curcumin inhibits ZIKV in a dose-dependent manner by preventing virus attachment to the cell surface without disrupting viral RNA . Recent studies have suggested a possible additional mechanism; specifically, curcumin inhibits dengue virus, a flavivirus that is related closely to ZIKV, by allosteric binding to the NS2B-NS3 protease. , Although curcumin shows potential as an antiviral, its effectiveness is hampered by its low solubility and instability in water .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite intensive global efforts, no specific treatment for ZIKV-associated diseases is currently available, which partially may be attributed to an incomplete understanding of the infection process. , Curcumin, a natural compound with pleiotropic activity, has demonstrated broad-spectrum antiviral properties. Experimental data have confirmed that curcumin inhibits ZIKV in a dose-dependent manner by preventing virus attachment to the cell surface without disrupting viral RNA . Recent studies have suggested a possible additional mechanism; specifically, curcumin inhibits dengue virus, a flavivirus that is related closely to ZIKV, by allosteric binding to the NS2B-NS3 protease. , Although curcumin shows potential as an antiviral, its effectiveness is hampered by its low solubility and instability in water .…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive global efforts, no specific treatment for ZIKV-associated diseases is currently available, 19 which partially may be attributed to an incomplete understanding of the infection process. 20 , 21 Curcumin, a natural compound with pleiotropic activity, has demonstrated broad-spectrum antiviral properties. 22 24 Experimental data have confirmed that curcumin inhibits ZIKV in a dose-dependent manner by preventing virus attachment to the cell surface without disrupting viral RNA.…”
Section: Introductionmentioning
confidence: 99%